Predicting future cancer incidence by age, race, ethnicity, and sex. Issue 1 (January 2023) - Garner, Wesley B.; Smith, Benjamin D.; Ludmir, Ethan B.; Wakefield, Daniel V.; Shabason, Jacob; Williams, Grant R.; Martin, Michelle Y.; Wang, Yuefeng; Ballo, Matthew T.; VanderWalde, Noam A.
Abstract: Introduction: Cancer remains a substantial burden on society. Our objective was to update projections on the number of new cancer diagnoses in the United States by age, race, ethnicity, and sex through 2040. Materials and Methods: Population-based cancer incidence data were obtained using Surveillance, Epidemiology, and End Results (SEER) data. Population estimates were made using the 2010 US Census data population projections to calculate future cancer incidence. Trends in age-adjusted incidence rates for 23 cancer types along with total cancers were calculated and incorporated into a second projection model. Results: If cancer incidence remains stable, annual cancer diagnoses are projected to increase by 29.5% from 1.86 million to 2.4 million between 2020 and 2040. This increase outpaces the projected US population growth of 12.3% over the same period. The population of older adults is projected to represent an increasing proportion of total cancer diagnoses with patients ≥65 years old comprising 69% of all new cancer diagnoses and patients ≥85 years old representing 13% of new diagnoses by 2040. Cancer diagnoses are projected to increase in racial minority groups, with a projected 44% increase in Black Americans (from 222, 000 to 320, 000 annually), and 86% in Hispanic Americans (from 175, 000 to 326, 000 annually). Discussion: The landscape of cancer care will continue to change over the next several decades. The burden of disease will remain substantial, and the growing proportion of older and minority patients with cancer remains of particular interest. These projections should help guide future health policy and research priorities.